セールロンダーネ サンチ チガク セイブツ チョウサ タイ ホウコク 1989-1990 (JARE-31) - 小山内, 康人; オサナイ, ヤスヒト; 高橋, 裕平; タカハシ, ユウヘイ; 田結庄, 良昭; タイノショウ, ヨシアキ; 土屋, 範芳; ツチヤ, ノリヨシ; 林, 保; ハヤシ, タモツ; 蛭田, 真一; ヒルタ, シンイチ; et al. (1990)
P(論文) 第31次南極地域観測隊(JARE-31)夏隊のセールロンダーネ山地地学・生物調査は, 山地全域においてヘリコプターを用いて実施された。ヘリコプター偵察飛行及び調査慣熟のための陸路調査が1989年12月25日から29日にかけて実施されたのに引き続き, 本調査が1990年1月5日から30日まで行われた。そのほかにあすか観測拠点付近の小山塊における調査・観測が1月1日と1月31日に実施された。調査・観測は38日間におよんだ。今回の行動形態は, 内陸山地でヘリコプターを導入した日本南極地域観測隊としては初めての例であるので, 計画作成から実施経過までを通信, 装備, 食料などの設営面を含めて詳しく報告する。調査結果については現在, 整理・研究中であり, 今後個別に発表されるので, ここでは概要を述べるにとどめる。 The Sør Rondane field party as part of the summer party of the 31st Japanese Antarctic Research Expedition (JARE-31) carried out geological, biological and geodetic fieldwork in the whole area of the Sør Rondane Mountains for 38 days from December 25,1989 to January 31,1990. This fieldwork was conducted with the support of helicopter flights which were operated by the expedition members of JARE for the first time. Therefore, this paper describes the details of the operation planning and a summary of the fieldwork including logistics and weather report. The results of geological, biological and geodetic investigations will be described in separate papers. departmental bulletin paper